Evaluation of Nurses’ attitudes, behaviors, and barriers toward pressure ulcer prevention in neonatal and pediatric intensive care units - Mostafa, Osama Elshahat; Zakari, Nazik M. A.; Al Salem, Marwa (Frontiers in Pediatrics, 2024)
Pressure ulcers are a significant concern in pediatric care units, with prevalence rates ranging from 0.8% to 27%, leading to considerable physical and psychological challenges, especially in neonatal and pediatric intensive care units (NICU & PICU). This study uniquely examines nursing strategies tailored to these specialized care environments, focusing on the prevention of pressure ulcers at NICU and PICU. Using a descriptive design, data were gathered from eighty nurses through validated questionnaires, including a nurses' profile and a pressure ulcer survey.The study identified specific nursing strategies, barriers to implementation, and attitudes toward pressure ulcer prevention in NICU and PICU settings. Descriptive statistics were used to analyze mean scores and percentages, while inferential statistics identified significant associations between variables. The total attitude mean score was 3.57, with the highest positive score being 4.29 for "most pressure sores can be avoided" and the highest negative score 3.86 for "pressure sore prevention is a low priority for me." Most nurses (72.5%) conducted risk assessments on all patients, 60% had written prevention care plans, and 76.3% implemented preventive strategies. However, 76.2% cited barriers such as staff shortages and time constraints. Multivariate analysis revealed that nurses with over 10 years of qualification (OR=3.67) and permanent staff with over 10 years of employment (OR=4.31) had significantly higher odds of engaging in prevention practices. The use of a pressure ulcer grading tool (OR=2.49, P<0.05) and formal training (OR=3.14, P<0.05) were also significant factors. These findings emphasize the need for structured assessment tools, ongoing education, and fostering positive attitudes to effectively reduce pressure ulcers and enhance patient outcomes in NICU and PICU settings.